Bite your tongue: Antonin Artaud and the Neo-Avant-Garde - Bradnock, Lucy E. (Yale University Press, 2017)
This exhibition catalogue essay examines the reception in the United States of the work of French dissident surrealist Antonin Artaud, and its impact on visual art practice during the post-war period. I argue that artists including Wallace Berman, Bruce Conner, and Nancy Spero identified in Artaud a model for dismantling the structures of authority via the linguistic, material, and corporeal mode of delirium.